Prophetic Law and Social Engineering: The Interaction between Religious Legal System and Customary Local System in Respect to Maintain and Promote Religious Values in Indonesian National Legal System - Jawahir Thontowi; Wildan Syahamata Ady; Nooraini Dyah Rahmawati; Mahrus Ali (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Legal system development certainly cannot be separated from sociological developments that include customs, norms, culture, and religion. In terms of rapid economic development, no doubt, a country is required to have a rule of law that can accommodate these needs and could cover various sociological spectrums that exist and are constantly changing within its people. Indonesia as a country with the largest Muslim majority in the world, while the notion of the whole state is based on Pancasila with diverse customs and cultural norms is certainly faced with several challenges, one of which is the transformation and the implementation of living law that includes religious, as well as indigenous law into a state law. The field of economics as an example of a social event that continues to revolve, will significantly be affected in the development of legal and social science. Sharia law is no longer a codification of exclusive law limited to certain groups of people but has become a general rule not only in Indonesia but also internationally with the existence of Islamic banking system. This phenomenon certainly changes the view of the legal order that applies in society if the change is assessed through the eyes of the sociology of law in Indonesia.